2022
DOI: 10.1186/s12909-022-03688-x
|View full text |Cite
|
Sign up to set email alerts
|

Programs to encourage working as a general practitioner in rural areas: why do medical students not want to participate? A cross-sectional study

Abstract: Background In many countries, not enough students are interested to work as general practitioners in rural areas. To solve this problem, several, sometimes partly extracurricular, programs have been developed. Most of these programs are based on continuity, which means that students stay in a rural region for an extended period of time, by completing clerkships. Although the effects of these programs are positive, it is often difficult to motivate students to participate. The purpose of the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(96 reference statements)
0
1
0
1
Order By: Relevance
“…has long been a frequent topic in the literature. [1][2][3][4][5] Being a good clinical teacher is a complex phenomenon and the defining traits may never be fully understood. 6,7 Nevertheless, studies have identified some common characteristics of a good clinical teacher in medicine, such as medical knowledge, technical skills, a supportive learning environment, communication skills, and enthusiasm.…”
Section: Re ´Sumementioning
confidence: 99%
“…has long been a frequent topic in the literature. [1][2][3][4][5] Being a good clinical teacher is a complex phenomenon and the defining traits may never be fully understood. 6,7 Nevertheless, studies have identified some common characteristics of a good clinical teacher in medicine, such as medical knowledge, technical skills, a supportive learning environment, communication skills, and enthusiasm.…”
Section: Re ´Sumementioning
confidence: 99%
“…Llamativamente, la mayoría de estudiantes son conscientes de la importancia de la MF, sin embargo, solo unos pocos tienen preferencia por esta especialidad5. La escasez de médicos/médicas de familia es especialmente grave en el ámbito rural 6,7 . En línea con González López-Valcárcel y Barber Pérez 8 , podemos preguntarnos si lo que está en crisis es el modelo de AP de salud que se inició con la reforma de la década de 1980 en el espíritu de Alma Ata o la especialidad de MFyC.…”
Section: Introductionunclassified